Rodzinne gospodarstwa agroturystyczne na obszarach wiejskich województwa zachodniopomorskiego - Sammel, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
In the period of transformation in Poland after 1989 the possibilities to develop individual economic activity, including family business, grew. Presently, family businesses are the basis of world economy. One of the forms of family business are agricultural family farms, managed by an individual farmer and his family. A specific type of the enterprise characterizes agritourist farms. These enterprises continue their activity, in spite of changing economic situation and world crisis, playing an important economic and social role. With regard to the meaning of this form of tourism for sustainable development of the rural areas, the aim of this paper is the analysis of functioning of family agritourist farms in Zachodniopomorskie region.